Research on the Grades of Brittleness Sources Based on Safety Management - Hong, Gao; Jigan, Wang; Hu, Siyan; Huang, Zoe (Recent Patents on Computer Science, 2016)
Innovation team is a kind of complex systems, for the purpose of controlling its operations and ensuring team effectiveness, based on safety management, this paper uses brittleness theory of complex system and social network analysis to study the grades of brittleness sources, which means to find out the important members who affect the team seriously. This paper examines four recent patents about safety management and social network analysis, then it collects data from innovation team W in Nanjing area as an example to construct the network model and give the analysis process. The results show that there are 11 members whose grades of brittleness sources are 1, which means if they are interfered by disturbance factors, the whole team will be affected and even collapse. This finding will be very important to the teams’ safety management.
Keywords: innovation team